Lactic acid bacteria in fermentation of cereals for the production of indigenous Nigerian foods - Nwachukwu, E.; Achi, O. K. (Global Journal of Food and Agribusiness Management, 2011)
The lactic acid bacteria (LAB) involved during the spontaneous fermentation of cereals (maize,millet, sorghum) for the production of indigenous foods (‘akamu’, ‘kunu-zaki’) were quantified and identified. The lactic acid bacteria counts varied during the fermentation of the cereals while the titratable acidity (TTA) increased with reduction in pH. Identification of isolates using API 50CHL system was Lactobacillus plantarum, L. pentosus, L. cellbiosus, Pediococcus pentosaceus and Leuconostoc mesenteroides. The potential of the isolates as starter cultures was determined by inoculating pure culture of lactic acid bacteria on sterilized cereals. The pH of the inoculated sterilized cereals dropped steadily while the total viable counts of the lactic acid bacteria especially L. plantarum increased. Analysis of variance (ANOVA, p=0.05) indicated the significant difference between total viable counts of different isolates during fermentation. This study showed potentials of L. plantarum as a starter culture for industrial fermentation of maize for ‘akamu’ production.